The economic consequences of German unification: The impact of misguided macroeconomic policies - Jörg Bibow (Levy Economics Institute of Bard College, 2001)
Although the costs associated with moving an antiquated socialist economy toward its capitalist counterpart was anticipated to be significant, German industrial efficiency was expected to quickly overcome any challenges. Things turned out rather differently. Conventional wisdom blamed poor economic performance on unification. The government and the Bundesbank therefore put in place fiscal and monetary policies aimed at reducing borrowing and, in turn, containing the threat of inflation. The positive results (albeit in five years) supported this perception. The author of this brief, however, takes exception to the notion that these policies were effective in stabilizing the economy. His analysis shows that the country's poor economic performance dramatically dampened economic activity and led to an extended period of sluggish growth. Blame for anemic growth and high unemployment, he believes, should be placed squarely on the country's finance department and central bank rather than on unification.
Keywords: 330; Nationale Einheit; Öffentliche Finanzwirtschaft; Haushaltsdefizit; Finanzpolitik; Geldpolitik; Wirtschaftswachstum; Deutschland